Immune-mediated insights into clinical and specific autoantibodies in acute and chronic immune-mediated nodo-paranodopathies - Gonçalves, Marcus Vinícius Magno; Tomaselli, Pedro José; Marques Junior, Wilson (Arquivos de Neuro-Psiquiatria, 2025)
The recognition of the molecular structures, namely the node of Ranvier and the axonal regions surrounding it (the paranode and juxtaparanode), as the primary target for specific autoantibodies has introduced a new site for neurological location (microtopographic structures), in contrast to the prevailing understanding, in which lesions to neural macrostructures (roots, nerves, and/or plexus) were the focus of semiologists and electrophysiologists for topographic, syndromic, and nosological diagnoses. Therefore, there was a need to understand and characterize the components of these neural microstructures that are grouped in small regions within the nerve to optimize clinical and therapeutic reasoning.
Keywords: Neuropathies; Neuritis